Etiological Trends and Antibiotic Susceptibility of Bacterial Strains Causing Respiratory Tract Infections - Fareeha Adnan; Faisal IqbalAfridi; Nazia Kurshid (ziauddin University, 2024)
Background: Lower respiratory tract infections (LTRIs) are emerging as the most common infectious diseases of humans. Antibiotic resistance has increased in all the major pathogens therefore, this project engrossed on deﬁning the current drift of bacterial etiologies of respiratory tract infections among the patients and their antimicrobial susceptibility pattern. Methods: This cross-sectional study with non-probability consecutive sampling was conducted in the microbiology laboratory of Ziauddin Hospital. Bacterial isolates (163) were recuperated from respiratory sputum specimens obtained from patients with lower respiratory tract infections. The pathogens collected for study were Streptococcus pneumonia, Haemophilus influenzae, and Moraxella catarrhalis. Frequencies and percentages were computed for categorical variables like microorganism, gender, age, duration of lower respiratory tract infections, etc. Mean and standard deviation were calculated for quantitative variables like age and infection duration. Furthermore, duration of disease was stratiﬁed by post stratiﬁcation Chi Square with p value ≤ 0.05 was considered signiﬁcant. Results: Most commonly isolated pathogen is Moraxella catarrhalis 72.39% followed by Haemophilus influenza 14.72% and Streptococcus pneumonia 12.88%. For Streptococcus pneumoniae 47% sensitivity showed to Ampicillin, 52% Penicillin, 61.9% Erythromycin and 57% to Ceftriaxone. For Haemophilus influenzae 100%, sensitivity showed to Ceftriaxone, 100% Amoxicillin and 62.5% Co-trimoxazole. Similarly, for Moraxella catarrhalis 54% sensitivity was showed to Erythromycin, 100% Ceftriaxone and 27% with Levoﬂoxacin. Conclusion: Moraxella catarrhalis, Haemophilus influenzae and Streptococcus pneumoniae were the most common bacterial isolates recovered from LTRIs. We found M. catarrhalis resistant rate was elevated for Levoﬂoxacin, Streptococcus pneumonia for Co-trimoxazole and Haemophilus influenzae to all β-lactams. Keywords: Respiratory Tract Infection; Haemophilus influenzae; Moraxella catarrhalis; Streptococcus pneumonia.